POLIMORFISME ADENINE NUCLEOTIDE TRANSLOCATOR-2PADA POPULASI INDIVIDU NORMAL DAN LEBER’S HEREDITARY OPTIC NEUROPATHY - Lyrawati, Diana; Tambunan, Krisna Bayu; Handoko, Herlina Y; Sudoyo, Herawati; Marzuki, Sangkot (Fakultas Kedokteran Universitas Brawijaya, 2006)
In this study we investigated the polymorphism of ANT2, an integral protein of mitochondrial inner-membrane, in individuals of normal population and patients of a mitochondrial respiratory chain disease Leber’s Hereditary Optic Neuropathy (LHON). DNA sequencing analysis demonstrated that there were sequence variation in ANT2 namely base substitutions G332T, C699T, C1021T, insertion of C andT and deletion of A, C, and C at nucleotide 20, 1127, 1022, 1075 and 1123, respectively (numbering based on mRNA sequence). The G332T resulted in amino acid change (R111L) and was predicted to alter the hidrophobicity pattern of Ant2 protein. PCR-RFLP analysis with HhaI restriction enzyme showed that both 111R and 111L variants were found in normal population of Caucasian, Chinese, Indonesian-Javanese, Mandar, Batak Toba and Papuan at different ratio (59%:41%, 61%:39%, 78%:22%, 64%:36%, 77%:23%, and 80%:20% respectively). Similar PCR-RFLP analysis was performed on samples of individuals carrying mtDNA mutation G11778A with and without characteristic manifestation of LHON to determine whether the ANT2 polymorphism was associated with clinical manifestation of mtDNA mutation. The data showed that the distribution of 111R and 111L between the two groups was different (Fischer Exact: α=0,05; P=0,0262). The ratio was 79,07%:20,93% in the group with typical manifestation of LHON and 56.52%:43.48% in the group without LHON manifestation. Inferred from the data, 111L may have protective effect against the manifestation ofLHON, whereas 111R may induce the manifestation ofLHON. Further studies are warranted to clarify the potential roleof the polymorphism of R111L (G332T) of ANT2 as a nuclear modifier of the LHON G11778A mutations. Key words: Adenine nucleotide translocator; ANT2; polymorphism, Leber's Hereditary Optic Neuropathy.